Characterization of Freisa Wines from Piedmont (Italy) by Aroma and Element Profile - Rabezzana, Roberto; Malandrino, Mery; Abollino, Ornella; Bonometti, Elisabetta; Giordana, Alessia; Turco, Francesca; Volpi, Giorgio; Operti, Lorenza (Applied sciences, 2023)
The main purpose of this study was to characterize Freisa red wines from Piedmont (northern Italy) according to their volatile organic compounds (VOCs) and elemental composition. Moreover, the authors investigated whether it was possible to distinguish among the five different DOCs produced in Piedmont on the basis of these chemical parameters. The VOCs profile of Freisa wines was very similar, and the most abundant species detected were isoamyl alcohol, phenylethyl alcohol, ethyl octanoate, and diethyl succinate. Conversely, elemental composition allowed us to partially distinguish one Freisa DOC with respect to the others. Multivariate statistical analysis applied to elemental composition revealed differences among Freisa wines and other red wines from different regions of Italy. In particular, Freisa wines featured higher concentrations of Cr and Ni metals, which are strongly correlated with the composition of the soil of Piedmont. These two elements are hence good candidates as chemical markers for Freisa wines from Piedmont.